Should they stay or should they go? Negative interest rate policies under review - Joscha Beckmann; Klaus-Jürgen Gern; Nils Jannsen (International Economics and Economic Policy, 2022)
Negative interest rate policies (NIRP) have become an established monetary policy instrument in the toolkit of the ECB. We discuss NIRP in the euro area based on theoretical considerations and available empirical evidence. We find that NIRP had some positive impact on loan growth and investment in the euro area, but that the room to further loosen monetary policy via NIRP may be small. NIRP is discussed also in the context of the general monetary policy environment.
Keywords: G12; 330; Negative interest rates; Monetary policy